위내시경 검사 목적에 따른 검사 전 불안 정도와 불안 경험: 혼합연구방법의 적용 - 조성희; Cho Sunghee; 서은영; Suh Eunyoung E (Perspectives in nursing science, 2020)
Purpose: This mixed method study aimed to investigate patients’ level of anxiety and their experience of this before undergoing esophagogastroduodenoscopy (EGD). Methods: A total of 125 patients answered a questionnaire assessing their pre-EGD level of anxiety, and a total of 17 patients participated in individual interviews regarding their experience of EGD-related anxiety. The SPSS Software program was used for survey data analysis and content analysis was used for qualitative data. Results: The mean anxiety score was 40.00±9.86 and the factors related to anxiety levels were being female (p<.001) and being a relatively young age (20-30 years old, p=.004). There were no significant differences shown in level of anxiety according to the purpose EGD was performed for: screening, diagnosis, or disease follow-up. In the qualitative analysis, however, patients who underwent a follow-up procedure as a result of stomach cancer exhibited more complicated feelings of anxiety and helplessness than others. For those who underwent EGD for diagnostic reasons, they worried about the test results and were concerned about possible life changes after diagnosis. Those for whom EGD was performed for screening purposes expressed concern only in the event of EGD complications. Conclusion: This study explored the nature of pre-EGD anxiety according to the purpose of the procedure. Nurses and doctors should be aware that patients undergoing EGD may have different levels and experiences of pre-procedure anxiety.